P0404B CELLS FROM PATIENTS WITH GRANULOMATOSIS WITH POLYANGIITIS FAIL TO REGULATE T CELL INTERFERON GAMMA RELEASE BUT DO REGULATE OTHER ASPECTS OF T CELL ACTIVATION. (6th June 2020) - Puli, Srinivas; Appelgren, Daniel; Hellmark, Thomas; Segelmark, Mårten
Abstract: Background and Aims: Regulatory features of B-cells have gained increased attention in patients with systemic vasculitis, including granulomatosis with polyangiitis (GPA). The aim with this study was to investigate the frequencies and phenotypes of two putative regulatory B (Breg) cell populations and assess the capacity of B-cells from GPA patients to regulate T-cell activation. Method: 37 GPA patients (22 remission and 15 active) and 31 healthy controls (HC) were included for measurement of CD19 + CD24 high CD27 + (memory) and CD19 + CD24 high CD38 high (transitional) Breg cells, and 11 GPA patients in remission and 12 HC for the functional studies of B-cells. HC were matched for age and gender. Results: Memory Breg cells were reduced in GPA both during active disease and remission compared with HC, whereas transitional Breg cells did not differ between the groups. Memory Breg cells consisted of less CD25 + cells during both active disease and remission but expressed more PD-L1 and CD86 during remission compared with active disease and HC. B-cells from GPA patients regulated T-cell proliferation and IL-17a production but failed to regulate IFN-γ production (Fig 1). The levels of IFN-γ and the IFN-γ regulated cytokine CXCL10 were elevated in patient plasma. Conclusion: Despite reduced levels and altered phenotypes of memory Breg cells, the capacity of GPA patient B-cells to regulate T-cell proliferation and IL-17a production was unaffected. However, we found a profound inability of patient B-cells to regulate T-cell IFN-γ production. This alteration could be important for the persistent inflammation that continues during remission and results in the chronic relapsing nature of the disease